Effect of Oscillation Amplitude on the Residence Time Distribution for the Mesoscale Oscillatory Baffled Reactor - Wan Mohd Hafizuddin, Wan Yussof; S. S., Bahri; Phan, A. N.; Harvey, A. P. (Bangladesh University of Engineering and Technology, 2017)
A recent development in oscillatory baffled reactor technology is down-scaling the reactor, so that it can be used for the applications such as small-scale continuous production of bioethanol. A mesoscale oscillatory baffled reactor (MOBR) with central baffle system was developed and fabricated at mesoscales (typically 5 mm diameter). This present work aims to analyse the mixing conditions inside the MOBR by evaluating the residence time distribution (RTD) against the dynamic parameters of net flow Reynolds number (Ren) at 4.2, 8.4 and 12.6 corresponding to flow rates of 1.0, 2.0 and 3.0 ml/min respectively, oscillatory Reynolds number (Reo) between 62 to 622, and Strouhal number (Str) between 0.1 to 1.59. The effect of oscillation frequency and amplitude on RTD performance were studied at frequency, amplitude, and velocity ratio ranging from 4 to 8 Hz, 1 to 4 mm and 1 to 118, respectively. Effect of oscillation frequency has resulted in the variance of the RTD increased as the oscillation frequency increased from 5 Hz to 8 Hz and peak at 6 Hz of 0.264. A further increase in the frequency above 5 Hz caused the RTD to slightly broaden and positively skewed. At frequency of 5 Hz, the RTD profiles were close to Gaussian form for all tested amplitude values from 1 mm to 4 mm. At low amplitudes, i.e. xo = 1 mm, the variance exhibited its minimum around 0.842 at Reo =156. An increase in Reo above 300 resulted in increased in the variance rapidly to 1.28, and later eliminated the plug flow behaviour and the reactor behaved similar to a single continuous stirred tank reactor.